Biological N2 Fixation in the Upwelling Region off NW Iberia: Magnitude, Relevance, and Players - Moreira-Coello, Víctor; Mouriño-Carballido, Beatriz; Marañón, Emilio; Fernández-Carrera, Ana; Bode, Antonio; Varela, Marta M. (Frontiers in Marine Science, 2017)
The classical paradigm about marine N2 fixation establishes that this process is mainly constrained to nitrogen-poor tropical and subtropical regions, and sustained by the colonial cyanobacterium Trichodesmium spp. and diatom-diazotroph symbiosis. However, the application of molecular techniques allowed determining a high phylogenic diversity and a wide distribution of marine diazotrophs, which extends the range of ocean environments where biological N2 fixation may be relevant. Between February 2014 and December 2015, we carried out 10 one-day samplings in the upwelling system off NW Iberia in order to: 1) investigate the seasonal variability in the magnitude of N2 fixation, 2) determine its biogeochemical role as a mechanism of new nitrogen supply, and 3) quantify the main diazotrophs in the region under contrasting hydrographic regimes. Our results indicate that the magnitude of N2 fixation in this region was relatively low (0.001±0.002 – 0.095±0.024 µmol N m-3 d-1), comparable to the lower-end of rates described for the subtropical NE Atlantic. Maximum rates were observed at surface during both upwelling and relaxation conditions. The comparison with nitrate diffusive fluxes revealed the minor role of N2 fixation (<2%) as a mechanism of new nitrogen supply into the euphotic layer. Small diazotrophs (<10 µm) were responsible for all N2 fixation activity detected in the region. Quantitative PCR targeting the nifH gene revealed the highest abundances of two sublineages of Candidatus Atelocyanobacterium thalassa or UCYN-A (UCYN-A1 and UCYN-A2) mainly at surface waters during upwelling and relaxation conditions, and of Gammaproteobacteria γ-24774A11 at deep waters during downwelling. Maximum abundance for the three groups were up to 6.7 × 102, 1.5 × 103 and 2.4 × 104 nifH copies L-1, respectively. Our findings demonstrate measurable N2 fixation activity and presence of diazotrophs throughout the year in a nitrogen-rich temperate region.